2021
DOI: 10.1038/s41396-021-00967-1
|View full text |Cite
|
Sign up to set email alerts
|

Variable influences of soil and seed-associated bacterial communities on the assembly of seedling microbiomes

Abstract: Plants grown in distinct soils typically harbor distinct microbial communities, but the degree of the soil microbiome influence on plant microbiome assembly remains largely undetermined. We also know that the microbes associated with seeds can contribute to the plant microbiome, but the magnitude of this contribution is likely variable. We quantified the influence of soil and seed microbiomes on the bacterial community composition of seedlings by independently inoculating seeds from a single cultivar of wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 64 publications
12
82
0
Order By: Relevance
“…On the contrary, our results show that seeds of all plants tested are able to transmit microbes to their roots (a core set of seed-transmitted Proteobacteria, Fusarium, and Pseudozyma), and in most cases, these microbes go on to dominate the endosphere despite being grown in microbe-rich soil. Other publications corroborate the importance of vertical transmission in establishing root microbiomes: we have shown twice before that seed-derived bacteria are the dominant members of juvenile maize root microbiomes (Johnston-Monje et al, 2014, 2016, with similar observations having been made in wheat (Walsh et al, 2021), rice (Hardoim et al, 2012), Arabidopsis (Truyens et al, 2016), common bean (López-López et al, 2010, barley (Yang et al, 2017;Rahman et al, 2018), sunflower (Leff et al, 2017), and diverse crops (Barret et al, 2015). It has also been noted that these seed-transmitted microbiomes may change in abundance over time, first increasing during germination (Barret et al, 2015) and later being displaced by soil-derived microbes as plants age (Yang et al, 2017).…”
Section: Microbial Populations In Rootssupporting
confidence: 88%
“…On the contrary, our results show that seeds of all plants tested are able to transmit microbes to their roots (a core set of seed-transmitted Proteobacteria, Fusarium, and Pseudozyma), and in most cases, these microbes go on to dominate the endosphere despite being grown in microbe-rich soil. Other publications corroborate the importance of vertical transmission in establishing root microbiomes: we have shown twice before that seed-derived bacteria are the dominant members of juvenile maize root microbiomes (Johnston-Monje et al, 2014, 2016, with similar observations having been made in wheat (Walsh et al, 2021), rice (Hardoim et al, 2012), Arabidopsis (Truyens et al, 2016), common bean (López-López et al, 2010, barley (Yang et al, 2017;Rahman et al, 2018), sunflower (Leff et al, 2017), and diverse crops (Barret et al, 2015). It has also been noted that these seed-transmitted microbiomes may change in abundance over time, first increasing during germination (Barret et al, 2015) and later being displaced by soil-derived microbes as plants age (Yang et al, 2017).…”
Section: Microbial Populations In Rootssupporting
confidence: 88%
“…The seed-associated bacterial communities are generally simpler in terms of composition and diversity than communities from soils, seedlings and adult plant tissues ( Chesneau et al, 2020 ; Rochefort et al, 2021 ; Walsh et al, 2021 ). Bacteria within phylum Proteobacteria, including members from Pantoea spp.…”
Section: Discussionmentioning
confidence: 99%
“…During the last years more and more research focused on the indigenous seed microbiome and its potential beneficial members driving plant’s tolerance to biotic and abiotic stress factors [ 65 67 ]. Seed endophytes that successfully colonize seedlings have been suggested to be important research targets for improvement of seed treatment technologies [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indigenous seed microbiome harbors endophytes that are proposed as synergetic components of the innate plant immunity, as the rice seed endophyte Sphingomonas was able to confer resistance against Burkholderia plantarii in later plant development [ 74 ]. Ubiquitous taxa in wheat seedlings were found to derive from the seed microbiome, but also the soil microbiome had an important but variable influence [ 68 ]. A previous study on the barley seed microbiome observed that the contribution of the seed microbiome to the endophytic root microbiome changed with increasing plant development and seed endophytes became less dominant in the endophytic root microbiome [ 21 ].…”
Section: Discussionmentioning
confidence: 99%